Efficacy of Melatonin Administration Via Different Route on Reproductive Performance and Blood Mineral Profile in Chhotanagpuri Ewe - Choudhary, Pankaj K.; Ishwar, Ajay K.; Kumar, Pramod; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study aimed to evaluate the comparative efficacy of melatonin administration via different routes on reproductive  performance and blood mineral profile of Chhotanagpuri ewe. A total of forty-two non-pregnant, non-lactating healthy ewes, not  exposed to rams for 2 months, were allocated to seven equal groups each of six animals, viz., G1 (Normal day light control), G2 (Long day  control, 16-18 h light; sunlight + artificial light), G3 (Long day as G2 + 3 mg melatonin daily orally), G4 (long day as G2 + 1 mg melatonin  daily subcutaneous), G5 (Short day control, 8 hours sun light, rest darkness), G6 (short day as G5 + 3 mg melatonin daily orally), and G7  (short day as G5 + 1 mg melatonin daily subcutaneous). The melatonin treatment was given for one month to ewes of G3, G4, G6 and  G7 and then were exposed to ram for one month, i.e., from day 61st to 90th; whereas the ewes of normal, long day and short day control  (G1, G2, G5) were exposed to ram for one month from day 31st to 60th. Blood samples were collected from each animal, day before  the start of experiment (day 0) and thereafter, every 30 days for five occasions. The estrus induction response was cent per cent in oral  melatonin treated ewes (G3 and G6) compared to subcutaneous route (83.33%, G4 and 66.66%, G7) and controls (33.3 to 50.0%). After  melatonin treatment, the overall estrus induction response and subsequent lambing rate were improved. The serum calcium level was  significantly (p
Keywords: Chhotanagpuri ewe; Estrus response; Fertility; Melatonin; Mineral; Photoperiod